Temperature dependence of radiation resistance of scintillation detectors based on lead tungstate crystals - Burachas, S.F.; Ippolitov, M.S.; Manko, V.I.; Nikulin, S.A.; Vasiliev, A.N.; Apanasenko, A.L.; Vasiliev, A.N.; Uzunian, A.V.; Tamulaitis, G. (Functional Materials, 2009)
Effect of gamma irradiation on the radiation resistance of detection blocks based on lead tungstate crystals has been studied in +60 to -25°C temperature range. A decrease in the radiation resistance and in the initial light yield recovery rate has been observed at the crystal temperature decrease. For the qualitative interpretation of the experimental results, the cluster model is used that assumes the presence of tungsten oxide clusters in the regular PWO (PbWO₄) matrix. The induced absorption of PWO crystals has been shown to depend on the cluster defect (CD) chemical composition and to be due to its radiation-induced transformation. The temperature dependence of the crystal radiation resistance has been shown to be in correlation with that of the initial CD composition recovery time.